Qumran and Apocalyptic : studies on the Aramaic texts from Qumran - García Martínez, Florentino. (Studies on the Texts of the Desert of Judah, 1992)
The present volume contains a selection of studies on the Aramaic texts from Qumran, originally published in Spanish but thoroughly revised here, which investigate the contributions made by the Qumran manuscripts to the study of the Apocalyptic Tradition. The first three papers collected here are concerned with apocalyptic texts belonging to the Enochic Tradition ( Book of Noah, Books of Enoch, Book of Giants ) and show how the fragmentary copies found at Qumran have radically altered the way in which we understand them. The next two studies deal with two texts which were previously unknown and which stem from the Danielic Tradition ( 4QPrNab, 4QpsDan Ar ); they both notably enrich our knowledge of the traditions of Daniel. The last two studies discuss two Qumranic apocalypses ( 4Q246, 11QNJ ) which reveal the richness and the diversity of the theological conceptions circulating within the Apocalyptic Tradition. The book offers a most up-to-date survey of research on these manuscripts and makes a fresh contribution to the understanding of Qumran and of the Apocalyptic Tradition.